Aluminum air fuel cell cathode catalyst and preparation method thereof
The preparation of silver-modified nitrogen-doped carbon material catalysts through the mixing of conductive carbon black and graphene and specific process processing, solving the problems of high prices and poor stability of precious metal catalysts, and achieving high efficiency performance and low cost production of cathode catalysts in aluminum air fuel cell .
Patent Information
- Application Number
- CN202411249603.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-27
AI Technical Summary
Precious metal platinum and silver oxygen reduction catalysts limit the application of aluminum air batteries due to their expensive price and poor cycle stability.
The conductive carbon black is mixed with graphene and heat treatment, and silver acetate and hydrazine hydrate are added to obtain a silver-modified nitrogen-doped carbon material catalyst by ultrasonic and vacuum drying. The aluminum air fuel cell cathode catalyst is prepared through specific process steps.
The stability and electrocatalytic activity of the catalyst are improved, the cost of raw materials is reduced, the advantages of industrial production are provided, and the catalytic performance is superior.
Smart Images

Figure CN119208637A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of aluminum-air batteries, and specifically relates to an aluminum-air fuel cell cathode catalyst and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology, energy consumption is increasing day by day. However, traditional fossil energy has limitations such as non-renewable and greenhouse gas production. Therefore, it is becoming increasingly important to develop new energy sources that are green, pollution-free, renewable and have high energy density. Among them, aluminum-air batteries have the advantages of being environmentally friendly, pollution-free, high specific energy density and a wide range of raw material sources. They are the only choice for new green energy. The key electrode materials of the aluminum-air power system mainly include air cathode, aluminum anode and electrolyte. Among them, an important component of the air cathode is the catalyst. The role of the catalyst is to catalyze the oxygen reduction reaction of oxygen. Generally, the oxygen reduction reaction is a four-electron process with many elementary steps and complex possible reaction paths.
[0003] Commonly used precious metal catalysts are platinum-based catalysts, which show good catalytic activity when used as oxygen electrodes. Platinum has higher catalytic activity than other transition metals, which may be due to the presence of d-orbital holes. As a catalyst, platinum is used in small amounts and has high efficiency and long-lasting activity, making it an important component of the most commonly used alloy catalyst. Silver is one of the typical oxygen reduction catalysts, and silver has good conductivity and relatively stable physical and chemical properties. It is common for early air electrodes to use silver instead of platinum as a catalyst.
[0004] However, precious metals platinum and silver have high oxygen reduction catalytic performance, but their high price and poor cycle stability greatly limit the application of aluminum-air batteries. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides an aluminum air fuel cell cathode catalyst and a preparation method thereof. The technical problem to be solved by the present invention is achieved by the following technical solutions: A method for preparing a cathode catalyst for an aluminum-air fuel cell, comprising: S1, mixing conductive carbon black and graphene in a first ratio, adding the mixture into a beaker containing anhydrous ethanol, stirring the mixture, and performing ultrasonic treatment to obtain a first solution; S2, adding urea to the first solution, stirring, performing ultrasonic treatment, and placing the solution in a vacuum drying oven to dry to obtain a first mixture; S3, spreading the first mixture evenly on the bottom of the crucible, placing it in a tube furnace for high temperature treatment, passing nitrogen, and performing heat preservation treatment to obtain a second mixture; S4, crushing the second mixture to obtain a third mixture; S5, dissolving an appropriate amount of silver acetate in deionized water, adding the third mixture in an appropriate mass ratio, and then adding an appropriate amount of deionized water, stirring to obtain a second solution; S6, heating the uniformly mixed second solution, and adding an appropriate amount of aqueous ammonia to make the pH value of the solution 10, to obtain a third solution; S7, adding hydrazine hydrate dropwise to the third solution while continuously stirring, and after the reduction reaction in the solution no longer occurs, performing solid-liquid separation on the solution, and washing with water to remove impurity ions until the solution is neutral to obtain a fourth solution; S8. After filtering the precipitate in the fourth solution, put it into a vacuum drying oven to dry until the water is completely evaporated, and crush it to obtain an aluminum air fuel cell cathode catalyst.
[0006] In a specific embodiment, in step S1, the first ratio is 1:4, the stirring time is 20-50 min, and the ultrasonic treatment time is 20-50 min.
[0007] In a specific embodiment, in step S2, the mass ratio of conductive carbon black to urea is 1:4, the stirring time is 20-40 min, the ultrasonic treatment time is 20-40 min, the vacuum drying oven temperature is 60-80° C., and the drying time is 2-4 h.
[0008] In a specific embodiment, in step S3, the heating rate of the tubular furnace is 5-10°C / min, the temperature is 600-650°C, and the holding time is 2-5 h.
[0009] In a specific embodiment, in step S5, the concentration of silver acetate is 0.1 mol / L, the mass ratio of the silver acetate solution to the third mixture is 3-5:10, and the stirring time is 30-50 min.
[0010] In a specific embodiment, in step S6, the heating temperature of the second solution is 80-90°C.
[0011] In a specific embodiment, in step S7, the molar ratio of hydrazine hydrate to silver acetate is 1.2-2:1, and the stirring time is 10-30 min.
[0012] In a specific embodiment, in step S8, the temperature of the vacuum drying oven is 100-110° C., and the drying time is 6-10 h.
[0013] The present invention also provides an aluminum-air fuel cell cathode catalyst, which is obtained by the preparation method of the aluminum-air fuel cell cathode catalyst.
[0014] Beneficial effects of the present invention: The preparation method of the aluminum air fuel cell cathode catalyst of the present invention has simple process, low raw material price, and has the advantage of industrial production; moreover, the prepared silver-modified nitrogen-doped carbon material catalyst has good stability, high electrocatalytic activity, excellent oxygen reduction performance, and its starting potential and limiting current density.
[0015] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic flow chart of a method for preparing a cathode catalyst for an aluminum-air fuel cell provided by an embodiment of the present invention; Figure 2 (a)- Figure 2 (b) are the XRD spectra of the catalyst provided in Example 1 of the present invention and the Raman spectra of N / VC2 and Ag@N / VC2; Figure 3 (a)- Figure 3 (b) are the TEM spectrum of the catalyst provided in Example 1 of the present invention and a high-resolution TEM spectrum; Figure 4 (a)- Figure 4 (b) is the SEM-EDS spectrum of the catalyst provided in Example 1 of the present invention.
[0017] Figure 5 (a)- Figure 5 (d) are respectively the XPS broad spectrum, high-resolution Ag 3d narrow spectrum, high-resolution N 1s narrow spectrum and pyridine type of the catalyst provided in Example 1 of the present invention.
[0018] Figure 6 (a)- Figure 6 (b) Comparison of ORR curves of N / VC2 before loading and Examples 1-3 at 1600 rpm. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto. Example
[0020] See also Figure 1 , Figure 1 The present invention provides a schematic flow diagram of a method for preparing a cathode catalyst for an aluminum-air fuel cell, including: S1, mixing conductive carbon black and graphene in a first ratio, adding the mixture into a beaker containing anhydrous ethanol, stirring the mixture, and performing ultrasonic treatment to obtain a first solution; S2, adding urea to the first solution, stirring, performing ultrasonic treatment, and placing the solution in a vacuum drying oven to dry to obtain a first mixture; S3, spreading the first mixture evenly on the bottom of the crucible, placing it in a tube furnace for high temperature treatment, passing nitrogen, and performing heat preservation treatment to obtain a second mixture; S4, crushing the second mixture to obtain a third mixture; S5, dissolving an appropriate amount of silver acetate in deionized water, adding the third mixture in an appropriate mass ratio, and then adding an appropriate amount of deionized water, stirring to obtain a second solution; S6, heating the uniformly mixed second solution, and adding an appropriate amount of aqueous ammonia to make the pH value of the solution 10, to obtain a third solution; S7, adding hydrazine hydrate dropwise to the third solution while continuously stirring, and after the reduction reaction in the solution no longer occurs, performing solid-liquid separation on the solution, and washing with water to remove impurity ions until the solution is neutral to obtain a fourth solution; S8. After filtering the precipitate in the fourth solution, put it into a vacuum drying oven to dry until the water is completely evaporated, and crush it to obtain an aluminum air fuel cell cathode catalyst.
[0021] In a specific embodiment, in step S1, the first ratio is 1:4, the stirring time is 20-50 min, and the ultrasonic treatment time is 20-50 min.
[0022] In a specific embodiment, in step S2, the mass ratio of conductive carbon black to urea is 1:4, the stirring time is 20-40 min, the ultrasonic treatment time is 20-40 min, the vacuum drying oven temperature is 60-80° C., and the drying time is 2-4 h.
[0023] In a specific embodiment, in step S3, the heating rate of the tubular furnace is 5-10°C / min, the temperature is 600-650°C, and the holding time is 2-5 h.
[0024] In a specific embodiment, in step S5, the concentration of silver acetate is 0.1 mol / L, the mass ratio of the silver acetate solution to the third mixture is 3-5:10, and the stirring time is 30-50 min.
[0025] In a specific embodiment, in step S6, the heating temperature of the second solution is 80-90°C.
[0026] In a specific embodiment, in step S7, the molar ratio of hydrazine hydrate to silver acetate is 1.2-2:1, and the stirring time is 10-30 min.
[0027] In a specific embodiment, in step S8, the temperature of the vacuum drying oven is 100-110° C., and the drying time is 6-10 h.
[0028] In a specific embodiment, the crushing method includes grinding with an agate mortar, a pulverizer, or a ball mill; the stirring method includes magnetic stirring, a stirrer stirring, or mechanical stirring; and the solid-liquid separation method includes suction filtration and centrifugation.
[0029] The present invention also provides an aluminum-air fuel cell cathode catalyst, which is obtained by the preparation method of the aluminum-air fuel cell cathode catalyst. Example
[0030] The method for preparing the cathode catalyst of the aluminum-air fuel cell in this embodiment comprises the following steps: (1) Weigh 4 g of conductive carbon black Vulcan-72XC and 1 g of graphene, add 200 mL of anhydrous ethanol into a beaker, stir magnetically for 20 min, and treat with ultrasound for 20 min; (2) Add 16 g of urea to the reaction solution, stir magnetically for 20 min, ultrasonically treat for 20 min, place the sample in a vacuum drying oven, and dry it at 60 °C for 2 h; (3) The obtained mixture was placed in a tubular furnace for high temperature treatment, with nitrogen flowing through it, and the temperature was raised to 600 °C at a rate of 10 °C / min and kept at that temperature for 2 h; (4) Grind thoroughly using an agate mortar to obtain 15.8 g N / VC2 powder; (5) Prepare a 0.1 mol / L silver acetate solution. Take 6.32 g of silver acetate solution and add N / VC2 powder. Then add 300 mL of deionized water and stir magnetically for 30 min. (6) Heat the reaction solution to 80 °C, then slowly add ammonia water to adjust the pH of the solution to 10; (7) Take 0.8 g of 50% industrial hydrazine hydrate and add it dropwise into the reaction solution. Stir magnetically for 10 min. Filter the reaction solution and wash it repeatedly with water until it becomes neutral. (8) The obtained precipitate was placed in a vacuum drying oven at 105 °C for 6 h and then ground using an agate mortar to obtain the final sample of Ag@N / VC2.
[0031] The XRD pattern of the catalyst prepared in this example is as follows Figure 2 (a) is shown. The diffraction peaks at 38.16°, 44.28°, 64.43° and 77.47° are the (111), (200), (220) and (311) face-centered cubic Ag crystal planes, respectively. The sharp diffraction peaks mean that the prepared Ag has a high degree of crystallinity and there are no impurity peaks, indicating that silver acetate is completely reduced to Ag. Figure 2(b) is the Raman spectrum of N / VC2 and Ag@N / VC2 in this example. Ag modification improves the ID / IG value of the nitrogen-doped carbon material, further increases the structural defects of the carbon material, and promotes the catalytic performance of the catalyst.
[0032] Figure 3 (a) is a TEM spectrum of the catalyst prepared in Example 1 of the present invention. A local high-resolution TEM test was performed on the black and white boundary part of the figure. Figure 3 (b) By measuring the interplanar spacing, it was determined that it was a single substance of Ag, indicating that the Ag particles were successfully modified into nitrogen-doped carbon materials, but the silver particles were slightly aggregated.
[0033] Figure 4 (a) is the SEM-EDS spectrum of the catalyst prepared in Example 1 of the present invention. Figure 4 (b) It can be obtained that the diameter is between 50nm and 80nm, and both Vulcan-XC72 and CNT are modified; the N element is evenly distributed on the C element without obvious agglomeration, further indicating that the nitrogen doping effect of N / VC2 is good.
[0034] Figure 5 (a) is the XPS broad spectrum of the catalyst prepared in Example 1 of the present invention. It can be seen from the figure that the catalyst is mainly composed of four elements: C, N, O, and Ag. 5 (b) is the high-resolution Ag 3d narrow spectrum of the catalyst prepared in Example 1 of the present invention. Ag 3d5 / 2 and Ag 3d3 / 2 peaks are fitted at binding energies of 367.8 eV and 373.8 eV, respectively. The peak position difference between the two peaks is 6 eV, indicating that the Ag element exists in the form of metallic Ag, which is consistent with the XRD characterization results. Figure 5 (c) is the high-resolution N 1s narrow spectrum of the catalyst prepared in Example 2 of the present invention. The proportions of different nitrogen-doping types are calculated using the high-resolution N 1s data, as shown in FIG. Figure 5 As shown in (d), the proportions of pyridinic nitrogen are 32.5%, pyrrolic nitrogen is 22.2%, graphitic nitrogen is 26.9% and pyridinic nitrogen oxide is 18.4%. The nitrogen doping types are still mainly pyridinic nitrogen and graphitic nitrogen, indicating that the loading of Ag particles does not conflict with nitrogen doping. Example
[0035] The method for preparing the cathode catalyst of the aluminum-air fuel cell in this embodiment comprises the following steps: (1) Weigh 50 g Vulcan-72XC and 12.5 g graphene, add 2500 mL anhydrous ethanol into a beaker, stir with an electric stirrer for 30 min, and ultrasonicate for 30 min; (2) Add 200 g of urea to the reaction solution, stir with an electric stirrer for 30 min, ultrasonically treat for 30 min, and place the sample in a vacuum drying oven at 70 °C for 3 h; (3) The obtained mixture was placed in a tubular furnace for high temperature treatment, with nitrogen flowing through it, and the temperature was raised to 620 °C at a rate of 7 °C / min and kept at this temperature for 3 h; (4) crushing with a pulverizer to obtain 180.5 g N / VC2 powder; (5) Prepare a 0.1 mol / L silver acetate solution by adding 80 g of silver acetate solution to N / VC2 powder, then add 3000 mL of deionized water and stir with an electric stirrer for 40 min. (6) Heat the reaction solution to 85 °C, then slowly add ammonia water to adjust the solution pH to 10; (7) Take 15 g of 50% industrial hydrazine hydrate and add it dropwise to the reaction solution. Stir with an electric stirrer for 20 min. Filter the reaction solution and wash it repeatedly with water until it becomes neutral. (8) The obtained precipitate was placed in a vacuum drying oven at 105 °C for 8 h and then crushed using a pulverizer to obtain the final sample, Ag@N / VC2. Example
[0036] The method for preparing the cathode catalyst of the aluminum-air fuel cell in this embodiment comprises the following steps: (1) Weigh 2000 g Vulcan-72XC and 500 g graphene, add 10 L of anhydrous ethanol into a beaker, stir with an electric stirrer for 50 min, and ultrasonicate for 40 min; (2) Add 8000 g of urea to the reaction solution, stir with an electric stirrer for 40 min, ultrasonically treat for 40 min, and place the sample in a vacuum drying oven at 80 °C for 4 h; (3) The obtained mixture was placed in a tubular furnace for high temperature treatment, with nitrogen flowing through it, and the temperature was raised to 650 °C at a rate of 5 °C / min and kept at this temperature for 4 h; (4) crushing with a pulverizer to obtain 7500 g N / VC2 powder; (5) Prepare a 0.1 mol / L silver acetate solution. Take 3200 g of silver acetate solution, add N / VC2 powder, then add 10 L of deionized water, and stir with an electric stirrer for 50 min. (6) Heat the reaction solution to 90 °C, then slowly add ammonia water to adjust the pH of the solution to 10; (7) Take 400 g of 50% industrial hydrazine hydrate and add it dropwise into the reaction solution. Stir with an electric stirrer for 30 min. Centrifuge the reaction solution and wash it repeatedly with water until it becomes neutral. (8) The obtained precipitate was placed in a vacuum drying oven at 110 °C for 8 h and then ground using an agate mortar to obtain the final sample of Ag@N / VC2.
[0037] Figure 6 (a) is a comparison of the ORR curves of N / VC2 before loading and Examples 1-3 at 1600 rpm. Ag modification of N / VC2 improves both the starting potential and the limiting current density. The starting potential of the catalyst prepared in Example 1 is 0.867 V (vs. RHE), and the limiting current density reaches 6.98 mA cm-2. Figure 6 (b) is the CV curve of Example 1-3 under O2 conditions. The curve area of the obtained catalyst is larger, indicating that its capacitive properties are more obvious.
[0038] The method for preparing the cathode catalyst of the aluminum air fuel cell of the embodiment of the present invention has a simple process, low raw material price, and has the advantage of industrial production; moreover, the prepared silver-modified nitrogen-doped carbon material catalyst has good stability, high electrocatalytic activity, excellent oxygen reduction performance, and its starting potential and limiting current density.
[0039] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0040] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.
[0041] Although the present application is described herein in conjunction with various embodiments, in the process of implementing the claimed application, those skilled in the art may understand and implement other variations of the disclosed embodiments by viewing the drawings, the disclosure, and the appended claims. In the claims, the word "comprising" does not exclude other components or steps, and "one" or "an" does not exclude multiple situations. A single processor or other unit may implement several functions listed in a claim. Certain measures are recorded in different dependent claims, but this does not mean that these measures cannot be combined to produce good results.
[0042] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for preparing a cathode catalyst for an aluminum air fuel cell, characterized in that: include: S1, mixing conductive carbon black and graphene in a first ratio, adding the mixture into a beaker containing anhydrous ethanol, stirring the mixture, and performing ultrasonic treatment to obtain a first solution; S2, adding urea to the first solution, stirring, performing ultrasonic treatment, and placing the solution in a vacuum drying oven to dry to obtain a first mixture; S3, spreading the first mixture evenly on the bottom of the crucible, placing it in a tube furnace for high temperature treatment, passing nitrogen, and performing heat preservation treatment to obtain a second mixture; S4, crushing the second mixture to obtain a third mixture; S5, dissolving an appropriate amount of silver acetate in deionized water, adding the third mixture in an appropriate mass ratio, and then adding an appropriate amount of deionized water, stirring to obtain a second solution; S6, heating the uniformly mixed second solution, and adding an appropriate amount of aqueous ammonia to make the pH value of the solution 10, to obtain a third solution; S7, adding hydrazine hydrate dropwise to the third solution while continuously stirring, and after the reduction reaction in the solution no longer occurs, performing solid-liquid separation on the solution, and washing with water to remove impurity ions until the solution is neutral to obtain a fourth solution; S8. After filtering the precipitate in the fourth solution, put it into a vacuum drying oven to dry until the water is completely evaporated, and crush it to obtain an aluminum air fuel cell cathode catalyst.
2. The method for preparing the cathode catalyst of aluminum-air fuel cell according to claim 1, characterized in that: In the step S1, the first ratio is 1:4, the stirring time is 20-50 min, and the ultrasonic treatment time is 20-50 min.
3. The method for preparing the cathode catalyst of aluminum-air fuel cell according to claim 1, characterized in that: In the step S2, the mass ratio of conductive carbon black to urea is 1:4, the stirring time is 20-40 min, the ultrasonic treatment time is 20-40 min, the vacuum drying oven temperature is 60-80 °C, and the drying time is 2-4 h.
4. The method for preparing the cathode catalyst of aluminum-air fuel cell according to claim 1, characterized in that: In step S3, the heating rate of the tubular furnace is 5-10°C / min, the temperature is 600-650°C, and the insulation time is 2-5 h.
5. The method for preparing the cathode catalyst of aluminum-air fuel cell according to claim 1, characterized in that: In step S5, the concentration of silver acetate is 0.1 mol / L, the mass ratio of the silver acetate solution to the third mixture is 3-5:10, and the stirring time is 30-50 min.
6. The method for preparing the cathode catalyst of aluminum-air fuel cell according to claim 1, characterized in that: In step S6, the heating temperature of the second solution is 80-90°C.
7. The method for preparing the cathode catalyst of aluminum-air fuel cell according to claim 1, characterized in that: In the step S7, the molar ratio of hydrazine hydrate to silver acetate is 1.2-2:1, and the stirring time is 10-30 min.
8. The method for preparing the cathode catalyst of aluminum-air fuel cell according to claim 1, characterized in that: In step S8, the temperature of the vacuum drying oven is 100-110° C., and the drying time is 6-10 h.
9. An aluminum air fuel cell cathode catalyst, characterized in that: The cathode catalyst of an aluminum-air fuel cell is obtained by the preparation method of the cathode catalyst of an aluminum-air fuel cell as described in any one of claims 1 to 8.
